Development of a Radiographic Index for Periodontitis - Zeyad M. H. Shaker; Azin Parsa; Keyvan Moharamzadeh (MDPI AG, 2021)
The use of radiographic indices is noticeably diminished due to the lack of simplicity and standardisation among the existing ones. The aim of this study was to introduce a radiographic index to aid clinicians in determining the extent and severity of interproximal alveolar bone loss (iABL), in relation to individual root lengths, among patients suffering from periodontitis. A retrospective analysis of 50 anonymised dental panoramic tomograms (DPTs) of patients with periodontitis was conducted. Visual interpretation of iABL was recorded by a single investigator and by 20 volunteering clinicians for the 'worst site' in each quintet. Results were compared to a gold standard quantification method. Intra-examiner and inter-examiner agreement were measured using the Kappa coefficient and the intra-class correlation coefficient, respectively. Validity was assessed using Cramér's V test. The mean intra-examiner agreement on the severity and pattern of iABL was 0.808 (K) and 0.802 (K), respectively. A stronger overall inter-examiner agreement was noted when the severity in contrast to the pattern of iABL and presence/absence of furcation involvement were analysed. The statistically significant total mean agreement values from this correlation coefficient were 0.892 and 0.739, respectively. A very strong association between all the visual interpretations carried out by all participants and the gold standard measurements was evident. Within the limitations of this study, the proposed radiographic index may serve as a simple, yet valid and reliable, adjunctive screening tool to further assist clinicians in determining the extent and severity of iABL in patients with periodontitis.